THE IMPLEMENTATION OF PROCESS APPROACH IN TEACHING WRITING TO THE FIRST YEAR STUDENT OF SMA ISLAM T. HUDA BUMIAYU IN 2010/2011 ACADEMIC YEAR - NINGSIH, RINI STIYA (2011)
The subject of this descriptive research is the first year student of SMA Islam T. Huda Bumiayu in 2010/2011 academic year. The objective of this research is to describe the implementation of process-based approach in teaching writing to the first year student of SMA Islam T. Huda Bumiayu, using naturalistic study. The writer uses descriptive qualitative research. The writer gets the data of this research from event, informant, and document. An event is the events in this research are all of the activities occurred in the writing class. Informants are the English teacher and the students of first year of SMA Islam T. Huda Bumiayu. Documents are all of the written information related to the activity in the writing class. The method of collecting data are observation, interview, document and audio-visual materials of the classroom activity in writing class. The result of the research shows that Process-based approach is appropriate and effective approach in teaching writing for the first year student of SMA Islam T. Huda Bumiayu. By using this approach, the students are able to produce a piece of writing and know the nature of writing in every writing stage. They are enthusiastic and motivateed to take part in the classroom activities. They work collaboratively with other peers in discussing a task. The teacher gives large oppurtunities to them to experiment with their ideas. There are four basic stages in the writing process, those are; pre-writing, drafting, revising, and editing. The conference session completes the writing process. The teacher also adopts three steps of teaching cycle, namely; opening, core-learning, and closing.